Ceria and ceria-based nanostructured materials for photoenergy applications. (April 2017) - Xie, Shilei; Wang, Zilong; Cheng, Faliang; Zhang, Peng; Mai, Wenjie; Tong, Yexiang
Abstract: With the fast-growing populations and development, energy crisis have raised critical requirements for utilization of clean solar energy. Some effective methods to capture and convert the solar energy now include photocatalytic degradation, hydrogen production, dye-sensitized solar cells, and photocatalytic selective reaction of organic compounds and so on. As the key factors for the utilization of solar energy, many photocatalysts have been exploited and great achievements have been made. Ceria (CeO2 ), which possesses unique 4f electrons, has attracted much interest due to their special electronic and optical structures, outstanding physical and chemical properties. This review aims to provide an overview of present progress on the study of photocatalytic performance of the CeO2 and CeO2 -based materials for photo-degradation, solar hydrogen production and photo-selective reactions. We also discuss the factors which affect photocatalytic performance of these photocatalysts, including the morphologies, structure and constitution of the CeO2 and CeO2 -based nanomaterials. Moreover, the current challenges and future opportunities of the CeO2 and CeO2 -based materials for the capture and conversion of solar energy are also discussed. Graphical abstract: Highlights: An overview of present progress of CeO2 and CeO2 -based materials using photoenergy. Discussion of various factors on photocatalytic properties. Future challenges towards CeO2 and CeO2 -based materials photocatalytic processes.